Engineered nanomaterials for aviation industry in COVID-19 context: A time-sensitive review - Pathak, Sunil; Saha, Gobinda C.; Musfirah, Abdul Hadi; Jain, Neelesh K. (MDPI AG, Basel, Switzerland, 2021)
Engineered nanomaterials (ENMs) are catalyzing the Industry 4.0 euphoria in a significant way. One prime beneficiary of ENMs is the transportation industry (automotive, aerospace, rail car), where nanostructured multi-materials have ushered the path toward high-strength, ultra-impact-resistant, lightweight, and functionally graded engineered surfaces/components creation. The present paper aims to extrapolate much-needed ENMs knowledge from literature and its usage in the aviation industry, highlighting ENMs contribution to aviation state-of-the-art. Topics such as ENMs classification, manufacturing/synthesis methods, properties, and characteristics derived from their utilization and uniqueness are addressed. The discussion will lead to novel materials’ evolving need to protect aerospace surfaces from unfolding SARS-COVID-19 and other airborne pathogens of a lifetime challenge.